Komunikasi Terbuka, Rahasia PT Spindo Ciptakan Lingkungan Kerja Nyaman - Joandsa Noor Afry; Abdullah Kafa Bihi; Hafizh Rafi Argani; Achmad Dida Saputra; Tan Evan Tandiyono (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study examines the role of communication openness in enhancing employee job satisfaction at PT Spindo Surabaya, a leading steel pipe manufacturer in Indonesia. Using a qualitative approach, the research was conducted over two months through in-depth observation and interviews with two key informants: a regular employee and a chief/foreman. The findings indicate that open communication significantly contributes to a positive work environment, improves teamwork, accelerates problem resolution, and fosters trust and psychological safety. Open communication also encourages innovation, increases employee involvement in decision-making, and boosts motivation. However, challenges such as miscommunication and employees' reluctance to speak openly were identified. Leadership plays a crucial role in cultivating an inclusive and open communication climate. Overall, open communication between supervisors and subordinates is a vital foundation for building an adaptive, innovative, and employee-centric organizational culture at PT Spindo Surabaya